How the grinch stole christmas ebook - Dr. Seuss (Classic Seuss., 2014)
#1 NATIONAL BESTSELLER • Get in on the Christmas cheer with Dr. Seuss’s iconic holiday classic starring the Grinch and Cindy-Lou Who—guaranteed to grow your heart three sizes! Every Who down in Who-ville liked Christmas a lot...but the Grinch, who lived just north of Who-ville, did NOT! Not since “’Twas the night before Christmas” has the beginning of a Christmas tale been so instantly recognizable. From the Grinch and his dog, Max, to Cindy-Lou and all the residents of Who -ville, this heartwarming story about the effects of the Christmas spirit will warm even the coldest and smallest of hearts. Like mistletoe, candy canes, and caroling, the Grinch is a mainstay of the holidays, perfect for readers young and old.